The association between dietary inflammatory index and diabetic foot ulcers in type 2 diabetes: a case-control study - Alanazi, Sultan Mohammed; Alabonassir, Ohoud Aied; Almasabi, Saleh Hussain A.; Alhazmi, Khalid; Alotni, Majid Ali; Mirdad, Dahlia Soleman A.; Alghamdi, Salah (Frontiers in Nutrition, 2025)
BackgroundDiabetic foot ulcers (DFUs) are a major complication of type 2 diabetes mellitus (T2DM). This study examined the association between the Energy-adjusted Dietary Inflammatory Index (E-DII) and odds of DFUs.MethodsIn a case–control study, 100 patients with DFUs and 150 T2DM controls were recruited. Dietary intake was assessed using a validated FFQ, and E-DII scores were calculated. Logistic regression estimated odds of DFUs across E-DII tertiles.ResultsDFU patients had higher E-DII scores than controls (2.1 vs. 1.5, p < 0.001). E-DII scores were positively correlated with both ulcer duration (ρ = 0.32, p = 0.002) and PEDIS score (ρ = 0.45, p < 0.001). Multivariable logistic regression showed that higher E-DII scores were significantly associated with increased DFU risk (OR for highest tertile: 1.94 [1.02–3.67]).ConclusionOur findings suggest that a pro-inflammatory diet, as measured by the E-DII, is associated with an increased odds and severity of DFUs in individuals with T2DM.